VD_FINDINFO HC / 2009 / 160 vom 6. Mai 2009 - VD Tribunal cantonal (2009)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, CAPACITÉ DE DISCERNEMENT | 19 al. 1 CP, 19 al. 2 CP, 42 CP, 43 CP, 411 let. j CPP, 415 CPP